Desenvolvimento e usabilidade da plataforma digital Apneia Conecte para acompanhamento da funcionalidade de indivíduos com apneia obstrutiva do sono tratados com CPAP no Sistema Único de Saúde do Estado do Ceará - Dias, Ekaterine Araújo (2024)
Introduction: The treatment of obstructive sleep apnea (OSA) using public health services is rare in Brazil. The gold standard treatment is achieved by applying continuous positive airway pressure (CPAP). The results of CPAP treatment were dose-dependent and cost-effective. Managing the treatment of patients with OSA using CPAP in the public health system is challenging because this chronic health condition requires continuous treatment. In this context, technological tools can be used as adjuvants during the follow-up of these patients. The “ApneIA Conecte” platform is a technology to help physiotherapists monitor patients with OSA. Objectives: To develop and validate the ApneIA Conecte digital platform and its functionalities for monitoring patients with OSA treated with CPAP. Methods: This is a methodological study that describes the development and usability of the ApneIA Conecte platform (INP No: BR512023001697-7) accompanied by the analysis of dialogs of the chatbot that integrates it. The development of the platform followed the pillars proposed by Falkembach with analysis and planning, modeling, implementation, evaluation, maintenance, and distribution. In the usability validation process, 20 judges, 10 physiotherapists and 10 technology judges analyzed content, accuracy, authorship, update, audience, navigation and structure of the platform. The instrument used in this process was the System Usability Scale (SUS) and a brief questionnaire adapted from the Health-Related Website Evaluation Form Emory (HRWEF) instrument. The database management system used was Firebase, the Dart and JavaScript programing languages, in addition to the Flutter framework and WhatsApp Business Application Interface (API). Users’ interests were identified using numbers according to the registered options. Data were collected from the interactions of participants using CPAP with the chatbot on the ApneIA Conecte platform over three months. The dialog paths, accessed topics, unanswered topics, bugs, interaction time, and conversation quality were analyzed to calculate the fallback rate. Results: In the SUS Scale, 60% of the physiotherapists judges classified the platform as the “Best imaginable” and 50% of the IT judges classified it as “Excellent” and the total average score attributed by the SUS judges was 79.5 (excellent). Regarding the questions adapted from the HRWF instrument, 90% of the judges agreed that the platform adequately covers all aspects. The results demonstrate good acceptance of the chatbot, and the satisfaction scores at the end of the service were greater than 7. Regarding the most accessed paths, the most relevant information about OSA and its treatment through CPAP. Conclusions: The development of ApneIA Conecte and its usability allow the presentation of a new technological product created for physiotherapists who monitor patients with OSA, with the aim of expanding the clinical follow-up of this population. The implementation of a chatbot proved to be a viable strategy that allows automated interaction through WhatsApp® with agile, accessible, and satisfactory communication according to the opinions of CPAP users.